The Tax Effects of Investment in Marketable Securities on Firm Valuation: Discussion - Thompson, Rex (Journal of Finance, 1979)
Rex Thompson, The Tax Effects of Investment in Marketable Securities on Firm Valuation: Discussion, The Journal of Finance, Vol. 34, No. 2, Papers and Proceedings, Thirty-Seventh Annual Meeting, American Finance Association, Chicago, Illinois, August 29-31, 1978 (May, 1979), pp. 339-342